Composite layered overlay: micro-invasive approach - Daniele Rondoni (Эндодонтия Today, 2020)
To effectively meet the current function and aesthetic needs of modern dentistry,  composites must allow operators to easily replicate layerings without renouncing the restoration effectiveness and durability. This case report describes the composite layered overlay technique restorations of the mandibular posterior teeth that can successfully replace invasive direct restorations.